An Overview of Narrative Medicine in China - Liping GUO (Chinese Medicine and Culture)
This paper sketches the history and the author’s involvement in the development of narrative medicine in China. It also describes “narrative medicine with Chinese characteristics,” explaining why narrative medicine is regarded as a tool to materialize the medical humanities in clinical practice, and detailing the features of narrative medicine in China. The features include the wide acceptance of the “22334 model” of narrative medicine, and borrowing theories and practice from Traditional Chinese Medicine. Finally, the author argues that the medical humanities should be given a “Class-A discipline” status, and narrative medicine should be a class-B discipline under the medical humanities.